Penanaman Nilai-Nilai Ketauhidan Pada Anak Usia Dini Melalui Kearifan Lokal - Mahbubah, Latifatul; Rabbani, Didin Burhanuddin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Indonesia is the largest country with a Muslim population. Therefore, instilling monotheism (tauhid) in young children, where they are the nation's next generation, is very important, especially at this time. The onslaught of liberal currents that continue to emerge is a very serious threat and needs to be addressed as soon as possible. Kiyai Langgar in Teja Timur Village, Pamekasan District carries out activities to instill monotheism (tauhid) in early childhood and packages it using local wisdom, namely using regional languages, so that children not only learn monotheism (tauhid), but also learn regional languages that they do not learn in formal schools. This research was carried out using descriptive qualitative research with data collection techniques using interviews, observation and documentation. The results of the research show that this activity, which is carried out almost every day, is carried out using the listening-imitating method (sam’iyah syafahiyah) and collaborated with repeated learning (drill). Uniquely, this activity is contested every year to increase children's enthusiasm for learning